Diversity of Nutrition among Male and Female Ukrainian Students - Józef Bergier; Barbara Bergier; Anatolii Tsos (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
Adequate nutrition is one of the most important factors of a good state of health. The objective of the study was recognition of the mode of nutrition and behaviours related with concern about silhouette among students from the Ukraine. Materials and Method. The study was conducted in 2013 among 2,125 students, including 1,291 females and 834 males, from 12 study specialties at the National University in Lutsk. The method of a diagnostic survey was applied with the use of a questionnaire. The study showed significant differences in the regularity of consumption of meals to the benefit of males. Females, in their behaviours, more frequently avoided eating, felt fear of gaining weight, and lost control over eating. With respect to behaviours related with concern about silhouette, females significantly more often applied exercises in order to reduce body weight, while males in order to gain body weight. A positive behaviour in both sexes was a trace application of drugs and other pharmacological means to improve own silhouette.